CUSTOMER LOYALTY TO SHARIA BANKING - Muhammad Dwi Aprinandhi (Magister Akuntansi, Universitas Atma Jaya Makassar, 2023)
Islamic banking operates according to Islamic principles, does not charge interest in each of its activities, and applies profit sharing. This study aims to find out how consumer loyalty toward Islamic banking. This study uses a literature review research method to conclude customer loyalty toward Islamic banking. This study found that generally, consumer loyalty toward Islamic banking is due to Islamic banking being affiliated with religion, informative marketing campaigns carried out by banks, banking brands, and reputations that have emotional ties with consumers, and trust in products and services offered by banks, as well the unique characteristics based on sharia law, not because of the rate of return provided by Islamic banking. This study also shows that the implementation of CSR influences customer loyalty in Islamic banking carried out by banks and becomes the basis for recommending Islamic banking to others.